COVID-19: Fears and challenges of health professionals before the pandemic (Research, Society and Development, 2020)
Objective: To identify the fears and challenges of health professionals in the face of this pandemic scenario of COVID-19, in the hospital context. Methodology: This is an integrative literature review, carried out in November 2020 in the databases: LILACS, MEDLINE, and SCIELO, using the following descriptors: COVID-19; health professionals and pandemic. Results and Discussion:  10 articles were analyzed which showed that this pandemic scenario, added to the fear of the unknown and the daily challenges to which they are exposed, led to a scenario of fear and challenges for health professionals, especially those who work at the front line. care for patients victims of COVID-19. Among the main challenges, the adjustments of the work routine, lack of personal protective equipment, training, diagnostic tests, knowledge about the disease, reduced number of professionals, in addition to fear of contagion and the possibility of infecting their family members stood out. Conclusion: Thus, it is hoped that the study can contribute, in some way, with reflections regarding the challenges faced by these workers, also becoming a time to reflect on their fears and uncertainties, emphasizing the need of implementing safety measures guided by science to favor the reduction of negative impacts on these health professionals.